The Concordance of Platelet Counts on Hematology Analyzer with Thrombocytopenia Sample with Platelet Clump - Prabawa, I Putu Yuda; Lestari, Anak Agung Wiradewi; Wande, I Nyoman; Mahartini, Ni Nyoman; Herawati, Sianny; Cong, Tzeto Han (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Pseudo-thrombocytopenia is a pre-analytical issue commonly observed in clinical laboratory settings due to platelet aggregation or clumps. In cases of thrombocytopenia, it is essential to conduct a platelet count via Peripheral Blood Smear (PBS) to identify clumping and subsequently re-evaluate the platelet count. The examination of platelets can now be carried out through different methodologies offered by Hematology Analyzers, such as PLT-I, PLT-O, and PLT-F. The primary objective of this research was to evaluate the correlation and agreement of platelet count findings (PLT-I, PLT-O, and PLT-F) in samples displaying flagged platelet clumps between a Hematology Analyzer and PBS at Prof. dr. I.G.N.G. Ngoerah General Hospital, Bali. An analytical cross-sectional observational study was conducted on 71 samples of thrombocytopenia with platelet clump flagging on the Sysmex® XN-1000 Series Hematology Analyzer at Prof. dr. I. G. N. G. Ngoerah Hospital. SPSS version 26.0 and MedCalc were used to conduct statistical analysis. There was a significant difference in the PLT clump Fluorescence index (p = 0.001) between the sample groups with and without the clump, and there was a strong positive correlation of the PLT count results between the Hematology Analyzer (p <0.001) and PBS in the sample groups with and without the clump. The Bland-Altman mean bias was lowest in the sample group without clumps against PLT-I (0.39x103/ml; 95% LOA: -57.05-57.83) and highest in the sample group with a clump to PLT-F (105.38x103/ml; 95% LOA: -14.7-225.46). There is a strong positive correlation and concordance of platelet count results between the Hematology Analyzer and PBS. However, there is no concordance between the platelet count results from the Hematology Analyzer and PBS in the clump group.